2022
DOI: 10.1155/2022/3014123
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Regenerative Cell-Derived Exosomes Attenuate Experimental Colitis through Downregulation of Intestine Ferroptosis

Abstract: Background. Endometrial regenerative cells (ERCs) have been identified to ameliorate colitis in mice; however, whether exosomes derived from ERCs (ERC-exos) own similar effects on colitis remains unclear. Ferroptosis, an iron-dependent cell programmed death form, has been reported to promote inflammation in UC. Thus, in this study, whether ERC-exos can treat colitis and regulate intestine ferroptosis will be explored. Methods. In this study, iron, malondialdehyde (MDA) production, glutathione (GSH) synthesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Partially in line with these results, our study revealed that in the IL-1β-stimulated rat chondrocytes, cell viability was suppressed, Fe 2+ , ROS and MDA levels were elevated, while GSH levels were declined; conversely, these changes were neutralized by BMSC-Exos, thus suggesting that BMSC-Exos could hinder the IL-1β-induced chondrocyte ferroptosis. A previous report has also indicated that Exos derived from endometrial regenerative cells can enhance the levels of GSH but reduced the levels of iron, and MDA in the colon of colitis mice, thus down-regulating intestine ferroptosis and attenuating dextran sulfate sodium-induced colitis [33]. Moreover, BMSC-Exos have demonstrated protective effects on podocytes against ferroptosis induced by HBx overexpression by transferring miR-223-3p [34].…”
Section: Discussionmentioning
confidence: 93%
“…Partially in line with these results, our study revealed that in the IL-1β-stimulated rat chondrocytes, cell viability was suppressed, Fe 2+ , ROS and MDA levels were elevated, while GSH levels were declined; conversely, these changes were neutralized by BMSC-Exos, thus suggesting that BMSC-Exos could hinder the IL-1β-induced chondrocyte ferroptosis. A previous report has also indicated that Exos derived from endometrial regenerative cells can enhance the levels of GSH but reduced the levels of iron, and MDA in the colon of colitis mice, thus down-regulating intestine ferroptosis and attenuating dextran sulfate sodium-induced colitis [33]. Moreover, BMSC-Exos have demonstrated protective effects on podocytes against ferroptosis induced by HBx overexpression by transferring miR-223-3p [34].…”
Section: Discussionmentioning
confidence: 93%
“…HT29 cells were pretreated with or without ferrostatin-1 (1.0 μM) for 4 h and then treated with CO (5.0 μM) or 8h (1.0 or 5.0 μM) to detect lipid peroxidation levels. Also, an MDA assay kit (S0131S, Shanghai Titan) was used to determine the levels of MDA …”
Section: Experimental Sectionsmentioning
confidence: 99%
“…Also, an MDA assay kit (S0131S, Shanghai Titan) was used to determine the levels of MDA. 46 4.10. Western Blot Analysis.…”
Section: N-(4-(4-(4-methylpiperazin-1-yl)piperidin-1-yl)phenyl)-6-oxo...mentioning
confidence: 99%
“…For example, Zhang et al demonstrated that exosomes containing microsomal triglyceride transfer protein could decrease the lipid ROS level of cancer cells via regulating glutathione peroxidase 4 (GPX4) and SLC7A11 127 . EVs derived from MSCs or other progenitor cells could also induce the expression of GPX4, SLC7A11 and glutathione, thereby activating endogenous anti‐oxidative signaling pathway, 128–130 which endows the EVs with anti‐ferroptosis ability. Moreover, other signaling pathways including P62‐associated autophagy, ferritinophagy, or NRF2 pathway may also be involved in EV‐mediated ferroptosis suppression 131,132 .…”
Section: Evs Affect the Fate Of Cell Ferroptosismentioning
confidence: 99%
“…T A B L E 1 EVs effects on the fate of cell ferroptosis. 127 EVs derived from MSCs or other progenitor cells could also induce the expression of GPX4, SLC7A11 and glutathione, thereby activating endogenous anti-oxidative signaling pathway, [128][129][130] which endows the EVs with anti-ferroptosis ability.…”
Section: Evs Ameliorate Cell Ferroptosismentioning
confidence: 99%